EnglishTurkey's Efforts to Normalize Diplomatic Relations with Israel After Withdrawal of Ambassadors both of the Two Countries in 2018 - Hawa Salsabila; Haryo Prasodjo; Dedik Fitra Suhermanto (Universitas Komputer Indonesia, 2022)
This study aims to provide information and literacy for readers regarding Turkey's efforts towards normalizing diplomatic relations with Israel after withdrawal of both of their embassies. What makes it interesting is that several times the relationship between Turkey and Israel has progressed and regressed due to the unfinished Israeli attack on Palestine, besides that Turkey also defended Palestine. However, Turkey is currently trying to normalize its relations with Israel for national interest. This study concludes that efforts to normalize relations with Israel are not easy to do because of the efforts of Turkey which still wants to cooperate with the enemy of Palestine. The findings in this study are Turkey's interest in peace efforts with Israel from an economic, political, and security perspective; and efforts to normalize diplomatic relations between Turkey and Israel in 2022. This study will use descriptive research methods and qualitative data analysis techniques that explain how the Turkish government's efforts to normalize relations with Israel are between improving and deteriorating in addition to Turkey's efforts to continue to defend Palestine using secondary data. This study will use the concept of strategy normalization to explain the stages of normalization sought by Turkey in improving its diplomatic relations with Israel. Keywords: Diplomatic, Israel, Normalization, Turkey.